2019
DOI: 10.3390/su11184977
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Transformative Economy: Community-Based Ecotourism

Abstract: Ecotourism has a high potential impact on remote communities, by improving economic opportunity and natural resources conservation, and is increasingly accepted as an alternative livelihood for rural people. This study examines ecotourism development from the perspective of participation and economic impact for the Bousra people in Cambodia. A total of 237 households were selected as the sample size. Data collection was carried out with face-to-face interviews and analyzed using logistic regression and ordinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 39 publications
1
19
0
2
Order By: Relevance
“…The issue of ecotourism in general, e.g., [15][16][17]20,[26][27][28][29][30], and the sustainability of ecotourism, e.g., [31][32][33][34], is currently being studied by a number of authors.…”
Section: Source Definitionmentioning
confidence: 99%
“…The issue of ecotourism in general, e.g., [15][16][17]20,[26][27][28][29][30], and the sustainability of ecotourism, e.g., [31][32][33][34], is currently being studied by a number of authors.…”
Section: Source Definitionmentioning
confidence: 99%
“…They found that resilience can be measured and evaluated by considering socioeconomic dimensions. The "success" of rural communities depends on the development of local resources (including businesses, human capital, land, and natural resources), local control over these resources, and how these resources are used [45].…”
Section: Csr Practice and Com-r Modelmentioning
confidence: 99%
“…A synopsis of the Special Issue consists of the following contributions: Xie et al [13] conceptualized the use of Ostrom's [14] social-ecological systems framework in the context of nature reserves in China by presenting a novel approach (i.e., the hybrid psycho-economic model) and interlinking collective forest management via a dynamic analysis of three case studies. Kim et al [15] examined the notion of sustainable transformative economy based on community-based ecotourism in a remote area of eastern Cambodia. This contribution examined ecotourism development from the perspective of participation and economic impact.…”
Section: Synopsis Of the Contributionsmentioning
confidence: 99%